The apple dihydrochalcone phloretin suppresses growth and improves chemosensitivity of breast cancer cells via inhibition of cytoprotective autophagy. Issue 1 (8th December 2020) - Chen, Ming; Gowd, Vemana; Wang, Mingfu; Chen, Feng; Cheng, Ka-Wing
Abstract : Schematic representation of the effect of phloretin-induced inhibition of cytoprotective autophagy in breast cancer cells under glucose starvation stress. Abstract : The inhibitory effect and mechanism of the apple dihydrochalcone, phloretin, on breast cancer cell growth were evaluated in in vitro conditions simulating complete nutrition and glucose-restriction, respectively. In two breast cancer cell lines with different histological backgrounds, phloretin consistently exhibited much stronger activity against cell growth in glucose-limiting than in full media. RNA-seq analysis showed that key autophagy-related genes were downregulated upon phloretin treatment in both estrogen-receptor-positive MCF7 and triple-negative MDA-MB-231 cells. Immunoblotting verified significantly decreased expression of LC3B-II by phloretin in low-glucose and glucose-free media, but not in full medium. Together with the use of two pharmacological autophagy inhibitors, chloroquine and 3-methyladenine, and confocal microscopy of breast cancer cell lines transfected with GFP-LC3B, phloretin demonstrated a strong capability to suppress autophagic flux, which was likely mediated through downregulation of mTOR/ULK1 signaling, whereas the expression of canonical autophagy regulators ATG5 and ATG7 was not significantly affected. Phloretin also reversed tamoxifen- and doxorubicin-induced cytoprotective autophagy in the breast cancer cell lines, and this was manifested in its synergistic growth inhibitory effect with these chemotherapeutic agents. Furthermore, it was able to restore or enhance the chemosensitivity of a tamoxifen-resistant cell line. Taken together, our study has, for the first time, revealed that phloretin could effectively suppress glucose-starvation- and chemotherapeutic-induced cytoprotective autophagy in breast cancer cell lines likely through downregulation of mTOR/ULK1 signaling.